Multiobjective optimization of dimension and position of elliptical crush initiator on crashworthiness performance of square tube using response surface methodology - Hafid, M.; Istiyanto, Jos; Nasruddin, Nasruddin (Frontiers in Mechanical Engineering, 2023)
In this study, the crashworthiness performance of a thin-walled square steel-tube structure with an elliptical crush initiator under impact loading was investigated. The effect of the height, width, and distance of the crush initiator from the top of the tube on the crashworthiness performance was analyzed using several numerical simulations using ABAQUS Explicit. The response surface methodology was used to predict the crashworthiness performance indices, and optimization was performed to determine the optimal dimensions and position of the crush initiator. The optimization was aimed at minimizing the peak force (PF) while maximizing the mean crushing force (MCF), crush force efficiency (CFE), and specific energy absorption (SEA). The result was an elliptical crush initiator with a height of 15 mm, width of 24.784 mm, and distance of 15.08 mm. Validation was performed to verify these results. The optimal crush initiator effect resulted in a 10.12% decrease in the PF, 13.67% increase in the CFE, and 2.23% increase in the MCF. However, a slight decrease of 0.82% in SEA was observed.